Edukasi dengan Media Komik terhadap Efikasi Diri Upaya Pencegahan Kekerasan Seksual pada Anak Usia Sekolah - Ida Erni Sipahutar (Jurnal Gema Keperawatan, 2020)
Sexual violence is any sexual act, pursues to commit sexual acts, comments or suggests unintentional sexual behaviour, and assaults for sexual intimacy with coercion to children. The impacts of sexual violence can ruin the psychosocial, future growth and development of children. This research purposes to determine the impacts of giving education by using comic as media on the self-efficacy to prevent sexual violence for school-age children. This research is pre-experimental designs with the design of one group pre-test post-test design. The sample amounted to 70 people using the startified random sampling technique. The Wilcoxon test tested the results of the study of ρ-value was 0,001, it means that there was a significant influence on giving education by using comic as media on the self-efficacy to prevent sexual violence for school-age children at 3 Batubulan Kangin Elementary School in 2019. Based on the results of the research, it is expected that it will be a guideline for teachers to educate other students by developing similar media.